Implementation of the Selection Sort Algorithm to Sort Data in PHP Programming Language - Indah Purnama Sari; Al-Khowarizmi Al-Khowarizmi; Fanny Ramadhani; Oris Krianto Sulaiman (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2023)
The role of algorithms in software or programming is very important, so it is necessary to understand the basic concept of the algorithm. The sorting algorithm is, selection sort (sorting by selecting) is the process of sorting data according to certain rules so that they are ordered regularly. Sorting data consisting of some criteria have priority where the data is sorted by language PHP programming that provides the sort function to sort array datain ascending or descending order from smallest to largest. The sort function is sort data from smallest to largest digit or last letter of letters first each word prioritizes letters then numbers if the data is in that table data consists of a mixture of numbers and letters. The method used is searching the smallest element of the array and swaps it with the element in the first position, then this algorithm repeats the same thing again, namely looking for elements in second position, The process that will result from this system continues until all array elements successfully sorted.